Korelasi antara kemampuan fisik siswa dan prestasi akademik mereka - Priskila, Devanti Efat; Arief, Nur Ahmad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Physical fitness is often linked to various cognitive and academic benefits, with numerous studies suggesting that physical ability may influence students' learning outcomes. Understanding this relationship is crucial for promoting holistic education that balances physical and intellectual development. This study investigates the correlation between students' physical ability and academic performance using a quantitative approach and a descriptive research design. The sample was selected through purposive sampling. Data collection involved physical ability tests and academic performance scores obtained from students' reportbooks. The physical ability tests included the Vertical Jump, Sprint, Ruler Drop Test, Zigzag Run Test, Hand Wall Toss Test, and Pacer Test. Data were analyzed using correlation formulas to determine the relationship between each physical ability measure and academic performance. The results revealed varying degrees of correlation: the Vertical Jump test showed a direct correlation (r = 0.0026), the Sprint test indicated no significant correlation (r = -0.065), the Ruler Drop test demonstrated an indirect correlation (r = -0.013), the Hand Wall Toss test indicated a direct correlation (r = 0.009), the Zigzag Run test suggested an indirect correlation (r = -0.062), and the Pacer test showed an indirect correlation (r = -0.008). These findings suggest that some physical abilities may have a small direct or indirect relationship with academic performance, while others show no significant correlation. The findings suggest that creating well-rounded athletes requires attention to intellectual development alongside physical training, ensuring a balanced approach to nurturing future champions.